EFFECT OF GAGNE’S EVENTS OF INSTRUCTION ON ACADEMIC PERFORMANCE OF POSTGRADUATE FCPS RESIDENTS IN OBSTETRICS AND GYNAECOLOGY - Habib, Sadia (Journal of Ayub Medical College Abbottabad, 2024)
Background: Learning and teaching has been transformed from traditional teacher centered behaviorist approach to more preferred student-centered constructivist approach. Applying Gagne’s nine-step model is a very effective way to enhance systematic learning of students. This research assesses the integration of Gagne’s instructional model for teaching sessions of postgraduate residents in obstetrics and Gynaecology. Methods: This quasi-experimental study was performed on FCPS postgraduate residents (PGRs) of the department of Obstetrics and Gynaecology, Ayub Teaching Hospital, Abbottabad. Twenty PGRs were assigned into two groups and teaching sessions were conducted using traditional and Gagne’s instructional model. Knowledge tests were used before and after both teaching sessions in order to assess academic achievement. In the analysis of academic scores, mean score differences were analyzed by using paired t-test. Results: An enhanced performance was evident in the post-test results of the group of postgraduate residents taught by incorporation of Gagne’s instructional model in teaching sessions compared to the conventional teaching style. The PGRs taught by lessons based on Gagne’s nine events of instructions had significantly higher post-test marks of 76.8% and 78.4% compared to pretest marks of 66% and 63.8% in Group-A & B respectively, (t=4.52; p<0.01), boosting their learning effectiveness by up to 10.8 and 14.8%. Conclusion: Gagne’s nine events of instruction provide a practical and effective framework for enhancing student engagement, retention, and academic performance in medical education. The findings support the adoption of structured, student-centered teaching strategies like Gagne’s instruction model to improve educational outcomes in PGRs in low-resource settings.